The verification of the method for prescribing training intensity of endurance running - Usaj, A.; Douvillard, S. P. (Medicine & Science in Sports & Exercise, 1997)
Lactate threshold and OBLA ("Onset of Blood Lactate Accumulation"; La = 4mM) are used to indicate training intensity for endurance adaptation. The theory behind their use is that the physiological response at threshold intensity is similar to endurance training if running velocity is similar. Runners (N = 9) performed three running tests: A - with an increase in velocity every 400 m, B - with an increase every 1200 m, and C - where a series of 8 x 2000 m runs was repeated at constant velocity. Lactate threshold, OBLA, and maximum lactate steady state were determined, the latter in protocol C. Running velocities at lactate threshold and OBLA were different between A and B. The running velocity at maximum lactate steady state was similar to OBLA velocity in B but significantly different to A. The lactate level in the maximum lactate steady state was different than the OBLA levels in A and B. Heart rates were similar between A and B. These results indicate that depending upon the test used, and the index selected, suggested velocities to be used in training prescriptions will be different. Implication. Using the results of lactate threshold, OBLA, or maximum lactate steady state tests to determine training velocities will result in different values for training prescriptions. Before these tests are employed the reasons for differing results need to be reconciled.